Echinacoside ameliorates alcohol-induced oxidative stress and hepatic steatosis by affecting SREBP1c/FASN pathway via PPARα. (February 2021) - Tao, Zhi; Zhang, Lihu; Wu, Tao; Fang, Xianying; Zhao, Linguo
Abstract: Alcoholic liver disease (ALD) is one of the most common health problems for drinkers, especially in men. Echinacoside (ECH), a natural phenylethanoid glycoside welcomed by the market, has been shown to have a variety of biological activities, such as neuroprotective, anti-fatigue, anti-diabetes and so on. Here, the protective effect and the underlying mechanism of ECH on ethanol-induced liver injuries were studied. In vitro, the HepG2 cells were treated with ECH prior to ethanol. In vivo, C57BL/6 J mice were fed a Lieber-DeCarli ethanol liquid diet and gave with or without 100 mg/kg ECH for 10 days. Our experiments showed that ECH significantly enhanced the levels of antioxidants and reduced the level of ROS, thus attenuating ethanol-induced oxidative stress. Besides, ECH attenuated lipid accumulation caused by ethanol, as evidenced by oil-red O staining, histological examination and the quantification of TG and TC. Finally, ECH increased the level of PPAR-α, and reduced the levels of SREBP-1c and FASN. When PPAR-α inhibitor was introduced in the system, the effects of ECH on SREBP-1c and FASN were reversed. Taken together, our study suggest that ECH can protect against ethanol-induced liver injuries via alleviating oxidative stress and hepatic steatosis by affecting SREBP-1c/FASN pathway via PPAR-α. Highlights: Echinacoside prevented liver injury induced by binge ethanol. Echinacoside alleviated oxidative stress and hepatic steatosis during chronic ethanol exposure. Echinacoside inhibited hepatic steatosis partially by affecting the SREBP-1c/FASN pathway via PPAR-α.